Some remarks on Schopenhauer’s influence on Freud - Szmaglińska, Katarzyna (Folia Philosophica, 2009)
The paper deals with the idea of unconsciousness in A. Schopenhauer and Z. Freud. The author argues that despite the fact that Schopenhauer does not explicitly use this term, he proposed some ideas which might be considered as pioneering to Freud’s “discoveries”. The turn towards the hypothesis of the unconsciousness may be seen as the attempt to close the gap (caused by Descartes’ thought) between the mind and the matter (in epistemology) and between the man and the world (in ontology).